Benefits of Functioning and Evaluation of Assets Investments of Domestic Non-state Pension Funds (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article analyzes the current status of private pensions in Ukraine, including non-state pension funds. There are also examined the benefits of non-state pension funds in the domestic investment market. The article provides characteristic of types of pension funds and the features of each one. A comparative analysis of the recent years growth of open, corporate and professional non-state pension funds is also included. The author investigates the sources of assets formation by non-state pension funds and possible directions for their usage. There are shown legislated areas and limits for the investments of private pension funds. There is analyzed the current state of investing pension assets in Ukraine. There are investigated the problems of efficiency and security of investment of non-state pension funds and provided recommendations for fuller disclosure of their investment potential
Keywords: non-state pension system, non-state pension funds, assets of non-state pension funds, investing of pension assets